A Literature Survey on Road Accident Automobile Detection Using Image Processing and IoT - Kalligudd, Nagaraj B; Srinivas, Chetana (International Journal of Computer Sciences and Engineering, 2025)
A lot of life loss due to road accidents every day because of careless drives of drivers, Human life most important to save and to know cause .A system with newer technology needs to be work effectively to save the life of the injured people. In this paper we have done survey over different method for road accident detection and proposed algorithm using IoT and Image technique .An intelligent accident detection system, when the accident is met the number plate of vehicle number is captured and converted to texted form and location is send it to the cloud and nearby police station.